QUANTITATIVE AND QUALITATIVE ANALYSIS OF THE EFFECTS OF DIFFERENT EXPERIMENTAL TREATMENTS - Branko Krsmanović; Tijana Krsmanović; Milan Dolga (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
On a specimen of 98 tested girls in 5th grade of elementary school, aged 10 ± 6 months, 57 in the experimental group and 41 in the control group, the effects of the experimental treatment were monitored by Eurofi t Battery Test and the tests for evaluation of specifi c motor skills. In the process, beside Multivariate Analysis of Variance and Covariance, the effects were determined by Confi rmatory Factor Analysis in order to get to see qualitative changes on isolated factors. The results showed signifi cant differences between the groups and between the initial and fi nal conditions, which refers to the greater effi ciency of the experimental treatment applied. Qualitative changes in the groups were analyzed by Profi le Analysis and they confi rmed the effi ciency of experimental treatments, as well as the qualitative changes which can be analyzed further